Indonesia - Hidayat; La Taha; Haderiah; Putri Noviyanti (HIGIENE: Jurnal Kesehatan Lingkungan, 2022)
Fatigue is a condition in which a person feels very tired, tired or sleepy due to lack of sleep, prolonged physical and mental work, or feelings of excessive stress and anxiety. Boring or repetitive work can increase feelings of fatigue (Canadian Center for OHS, 5 2012). This study aims to determine the factor of work fatigue on inter-district bus drivers at the Manggala Trans Tana Toraja Otobus Company. This type of research is an analytical observational study with a cross sectional approach to determine the analysis of work fatigue factors on inter-district bus drivers in Tana Toraja. In collecting data, using questionnaires or interviews, for the main driver and the auxiliary bus driver for the Toraja-Makassar and Makassar-Toraja routes, the source of the data was obtained from respondents, namely people who responded or answered the researcher's questions, both written and oral questions. Based on the four variables studied, it shows the results of the work fatigue factor for inter-district bus drivers, namely there is no relationship between age and work fatigue for bus drivers, there is a relationship between driving duration and work fatigue for bus drivers, there is no relationship between working period and work fatigue for bus drivers. , and there is a relationship between sleep quantity and work fatigue on bus drivers at the Mangala Trans Autobus Company. Keywords: work fatigue, age, driving duration, working period, sleep quantity